2003
DOI: 10.1083/jcb.200304003
|View full text |Cite
|
Sign up to set email alerts
|

APP-BP1 mediates APP-induced apoptosis and DNA synthesis and is increased in Alzheimer's disease brain

Abstract: APP-BP1, first identified as an amyloid precursor protein (APP) binding protein, is the regulatory subunit of the activating enzyme for the small ubiquitin-like protein NEDD8. We have shown that APP-BP1 drives the S- to M-phase transition in dividing cells, and causes apoptosis in neurons (Chen, Y., D.L. McPhie, J. Hirschberg, and R.L. Neve. 2000. J. Biol. Chem. 275:8929–8935). We now demonstrate that APP-BP1 binds to the COOH-terminal 31 amino acids of APP (C31) and colocalizes with APP in a lipid-enriched fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
81
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(85 citation statements)
references
References 24 publications
3
81
1
Order By: Relevance
“…Chen et al 4 demonstrated that neurons expressing APP or APP (V642I) show an increase in APP-BP1 levels in lipid rafts, which is also observed in the hippocampal region of AD patients. This could explain why an elevated level of membrane APP increases the physical interaction between APP and APP-BP1 required for reducing APP-induced toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chen et al 4 demonstrated that neurons expressing APP or APP (V642I) show an increase in APP-BP1 levels in lipid rafts, which is also observed in the hippocampal region of AD patients. This could explain why an elevated level of membrane APP increases the physical interaction between APP and APP-BP1 required for reducing APP-induced toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…1 The binding site has been identified as the carboxyl-terminal 31 amino-acid residues of APP. 4 This suggests the possibility of a similar interaction between dAPP-BP1 and APPL. Interaction was examined by an in vitro binding assay using a bacterially expressed GST-tagged APPLC63 (APPL carboxyl-terminal 63 amino-acid residues), GST, and in vitro expressed 35 S-methionine-labeled dAPP-BP1.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Involvement of APP‐BP1 and the formation of Aβ plaques have been proposed (Chen, Liu, McPhie, Hassinger, & Neve, 2003). It is well known that APP undergoes γ‐secretase cleavage to produce Aβ.…”
Section: Pathological Contributions Of the Ubiquitin–proteasome Systementioning
confidence: 99%
“…These regulatory mechanisms suggest that when the expression level of APP‐BP1 is elevated, the levels of Aβ would decrease accordingly. Nevertheless, this idea remains controversial with the observation that APP‐BP1 expression has been shown to increase in AD‐affected regions of the brain (Chen et al., 2003). In an important way, overexpression of APP‐BP1 has been shown to trigger cytoplasmic relocalization of NEDD8 within neuronal cells, which may erroneously incorporate into the ubiquitin chains of degradation substrates and disrupt the subsequent proteolytic activities instead of enhancing the ubiquitination activity (Chen et al., 2012).…”
Section: Pathological Contributions Of the Ubiquitin–proteasome Systementioning
confidence: 99%